FAKTOR-FAKTOR YANG MEMPENGARUHI NET INTEREST MARGIN (BANK GO PUBLIK TAHUN 2008 S/D 2011) - RMP, Margaret; Nurmayanti, Poppy (Jurnal Tepak Manajemen Bisnis, 2014)
The purpose of this study is to examine the factors that affect the net interest margin of the Go public Bank listed on the Indonesia S tock Exchange (BEI) in the period 2008 to 201 1. There are 15 banking companies r ecorded in BEI, which made the study population obtained from the Annual Report of the Bank as determined by Bank Indonesia. Data analysis method used is multiple linear regression analysis and hypothesis testing use t-statistics and f-statistics in level of significance 5%. Based on the statistics t test showed that the capital adequacy ratio, return on assets, loan-to- deposit ratio, operating expenses to operating income and size have a significant effect on the net interest margin. While, non-performing loans and did not significantly affect the net interest margin. In addition, the normality test and include the classical assumption that multicolinearity , heteroscedasticity test and autocorr elation test. During the obser vation period of the study show that the data are normally distributed. Based on the test multicollinearity, heteroscedasticity test and autocorrelation test found no variables that deviate from the classical assumptions, it is shown that the available data are qualified to use the model of multiple linear regression equation. The results together indicate that the variable return on assets, loan-to-deposit ratio, capital adequacy ratio, non- performing loans and operating expenses to operating income and size has a significant influence on the bankâ s net interest margin is going public. Thus the bank is expected to consider the factors that affect the net interest margin that banks more efficient performance.Keywords: CAR, NPL, BOPO, ROA, LDR,Size dan NIM.